2016
DOI: 10.1002/anie.201600351
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Induced Catalytic Amplification Reaction for Readout of Receptor‐Mediated Cellular Forces

Abstract: Mechanics play a fundamental role in cell biology, but detecting piconewton forces is challenging due to the lack of accessible and high throughput assays. Herein we report the mechanically-induced catalytic amplification reaction (MCR) for readout of receptor-mediated forces in cells. Mechanically labile DNA duplexes presenting ligands are surface immobilized such that specific receptor forces denature the duplex and thus expose a blocked primer. Amplification of primers is achieved using an isothermal polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Second generation MTFM probes have further improved the dynamic force range, 27 sensitivity 28,29 and stability. 3033 We recently developed a gold nanoparticle (AuNP)-based DNA tension probe to directly image the TCR-pMHC forces on immobilized ligands and revealed that T-cells may harness mechanics for enhanced antigen sampling and discrimination. 34 …”
mentioning
confidence: 99%
“…Second generation MTFM probes have further improved the dynamic force range, 27 sensitivity 28,29 and stability. 3033 We recently developed a gold nanoparticle (AuNP)-based DNA tension probe to directly image the TCR-pMHC forces on immobilized ligands and revealed that T-cells may harness mechanics for enhanced antigen sampling and discrimination. 34 …”
mentioning
confidence: 99%
“…Inspired by the ELISA and PCR assays that revolutionized molecular biology, our lab developed a catalytic amplification strategy to convert mechanical forces into an amplified fluorescent readout, coined mechanically induced catalytic amplification reaction (MCR) . In initial proof‐of‐concept experiments, MCR leveraged the TGT as a peak force transducer.…”
Section: Dna‐based Force Probes To Map Piconewton Forces Within Cellsmentioning
confidence: 99%
“…C) Bar graph showing the ability of MCR to differentiate integrin antibodies that block different integrin subtypes. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Dna‐based Force Probes To Map Piconewton Forces Within Cellsmentioning
confidence: 99%
“…[48] Depending on the detection strategy used, these devices are divided into electrochemical, optical, and mass-sensitive sensors.A sa ne xample,a ptamers can be tagged with aredox-active moiety like methylene blue (MB) or ferrocene (Fc) to transduce conformational changes upon target binding into an electrochemical signal that originates from the labels closer proximity to the electrode ( Figure 3A). [52,55] Indeed, this approach proved extremely sturdy and useful to elucidate fundamental Angewandte Chemie Kurzaufsätze processes in cell biology,such as the determination of pulling forces exerted by integrin or T-cell receptors. In this approach, one reporter serves as the target responsive sensor,w hereas the other one acts as ar eference,w hich decreases signal drift events to less than 2% in complex media such as whole blood.…”
Section: Dna Chips For Nanomaterials Assemblymentioning
confidence: 99%
“…[51,54] While the above methods allow for in vitro measurement of biologically relevant forces in the pico-to nanonewton range,i ti sd ifficult to apply these techniques to the study of mechanical forces emanating from living cells,w hich often trigger their fundamental programs like adhesion, migration, and differentiation by mechanical forces.T os implify the quantification of cellular pulling forces,s urfaces bearing fluorescently labeled DNAhairpin structures were developed by Salaitasg roup (Figure 3D). [52,55] Indeed, this approach proved extremely sturdy and useful to elucidate fundamental Angewandte Chemie Kurzaufsätze processes in cell biology,such as the determination of pulling forces exerted by integrin or T-cell receptors.…”
Section: Dna Chips For Nanomaterials Assemblymentioning
confidence: 99%